Names of people groups: semantic aspects - Ходоренко, Анна Викторовна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The article deals with a semantic description of general types of people groups names (PGN). Main semantic peculiarities are supposed to be given in the article. Different examples of the names of various people groups (names of commercial enterprises, political parties, creative groups) are suggested to illustrate PGN types and their semantics. The problem considered in this article has to do with the development of semantic description of different names of people groups. Languag material consists of a diverse groups of people including professional unities, the Internet’s groups, organizations, political societies etc. Theoretical basis of the present study is based on domestic and foreign works considering linguo-stylistic, pragmatic, semantic, lexical and other aspects of linguistic units. The aims and objectives are to consider semantic aspects of names initially considered to be empty from semantic point of view and proved to be deeply motivated.